2010
DOI: 10.1086/653424
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr Virus–Associated Hemophagocytic Lymphohistiocytosis in Adults Characterized by High Viral Genome Load within Circulating Natural Killer Cells

Abstract: Epstein-Barr virus (EBV)-associated hemophagocytic lymphohistiocytosis (HLH) is a rare and aggressive disease usually encountered in the context of primary EBV infection. In most analyzed cases, EBV has been found predominantly in T cells. We describe the novel finding of high EBV genome numbers within circulating natural killer cells in adult patients with EBV-HLH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 17 publications
0
41
0
4
Order By: Relevance
“…It is well established that EBV and its antigens induce massive release of cytokines, thereby activating monocytes/macrophages and causing damage in multiple organs [11]. A series of Japanese-based studies have found that T cells and NK cells are targeted by EBV infection in patients with EBV-HLH [12, 13]. Fox et al [13] reported abundant EBV genomes (12,900–1,816,550 genomes/10 6 cells) in the circulating NK cells of such patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that EBV and its antigens induce massive release of cytokines, thereby activating monocytes/macrophages and causing damage in multiple organs [11]. A series of Japanese-based studies have found that T cells and NK cells are targeted by EBV infection in patients with EBV-HLH [12, 13]. Fox et al [13] reported abundant EBV genomes (12,900–1,816,550 genomes/10 6 cells) in the circulating NK cells of such patients.…”
Section: Discussionmentioning
confidence: 99%
“…This disease is also frequently seen in east Asian countries, 11 and involves a clonal expansion of EBV ϩ T or NK cells, which produce inflammatory cytokines that induce the activation of macrophages and hemophagocytosis. [21][22][23] Apart from these systemic diseases, accumulating evidence indicates that 2 cutaneous diseases, hydroa vacciniforme and severe mosquito bite allergy, are closely associated with EBV ϩ T or NK cells. Hydroa vacciniforme is characterized by recurrent vesiculopapules usually occurring on sunexposed areas and seen in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…In EBV-related haemophagocytic lymphohistiocytosis, EBV-infected CD8 T cells and natural killer cells are thought to trigger haemophagocytosis and the associated ‘cytokine-storm’/systemic inflammatory response syndrome (SIRS) directly 24…”
mentioning
confidence: 99%